Organ Laundering in Nigeria, Socio-Psychological Implications - Uwaoma, Nkwam .C.; Njoku, Agnes Osita; Uwaoma, Adeline .O. Nkwam; Udeagha, Chinweike .F. (Richtmann Publishing, 2011)
This paper examined the concept of organ laundering, it’s sustaining factors, the various organs highly harvested and the sociopsychologicalimplication of the whole practice. Among the Nigerian etiological factors for organ laundering are penury, lengthening patientwaiting lists, greed and deception of victims, boom and life organ donors and better quality of life organs. Behavioural tension, fear,suspicions, violence, confusion, somatic pains and loss of brotherhood, freedom and recreation were unveiled as socio-psychologicalimplications of organ laundering in Nigeria. The following were recommended:- Nigerians, especially the youths, should endeavour to be atthe right place with the right people and at the right times; Girls specifically, should avoid flexing ( mixing up with unknown people, forentertainments or going to unknown destinations); Sick persons, Ladies for abortion and people seeking medical attentions should go toknown or traceable hospitals to avoid being butchered; Government and the general public should assist to fight poverty and corruption,and build high morals in people and then create job opportunities.